2016
DOI: 10.18178/jtle.4.2.147-153
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing and Modeling a City’s Spatiotemporal Taxi Supply and Demand: A Case Study for Munich

Abstract: This paper presents a method for studying supply and demand in a taxi network in time and space by using the example of Munich. First, we introduce the necessary data collection that is linked to a fleet management system (FMS) operated by a local taxi agency and create a statistically sound database, which represents the mobility behavior on a trip level. Second, we derive key figures describing the city's taxi characteristics. Here both the temporal taxi supply and demand of 420 taxis over a period of 19 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…A study on the Asian market revealed spatio-temporal patterns to help taxi drivers spend less time for cruising [1]. Another example of demand prediction introduced based on city district scale in Munich, revealed timedvariant demand prediction for individual districts [2]. Mineta National Transit Consortium presented a report with results of taxi demand across time and space using GPS data from taxis [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study on the Asian market revealed spatio-temporal patterns to help taxi drivers spend less time for cruising [1]. Another example of demand prediction introduced based on city district scale in Munich, revealed timedvariant demand prediction for individual districts [2]. Mineta National Transit Consortium presented a report with results of taxi demand across time and space using GPS data from taxis [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A fleet of 550 taxis served ≈10 M customer trips between 2015 and 2020. The data are being continuously retrieved from the fleet management interface, which is usually used for dispatching by the local taxi agency [30]. The data are directly provided by the dispatching agency with full information about trip start, trip end, and driven route.…”
Section: Taxi Datamentioning
confidence: 99%
“…The recent popularity of e-hailing taxi services has generated substantial interest in developing efficient taxi demandsupply prediction algorithms [5], [6], [7], [8]. In the past, taxi demand-supply prediction was mainly formulated as a classical time-series forecasting problem.…”
Section: A Related Workmentioning
confidence: 99%